POLA PENGASUHAN ANAK PADA KELUARGA BURUH WANITA DI PT. BLAMBANGAN FOODPACKERS INDONESIA PENDEKATAN STRUKTURAL FUNGSIONAL - Lestari, Anies Yuni; Tamim, Imron Hadi; Suka Arjawa, I Gusti Putu Bagus (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT The Economic condition, job opportunity, assumption about independent women, and self-satisfaction are the reasons why women work as labors at PT. Blambangan FoodPackers Indonesia. Worked as labors make women have less intensive interaction toward their children because of full working hours. Therefore, it is a need to find the arrangement strategy of parenting model. The aim of this research refer to model of parenting which adopted by women labors and her families to their children. This research will also explain the dissention of parenting model between one woman worker family to the other women worker families. Structural functional theory by TalcottÂ Parsons was used to analyze the process of parenting model. Qualitative method and descriptive approach was used as a method on this research. The result of this research showed that women labors applied authoritative parenting model/democratic. Temporary parenting model was done by grandmother and grandfather as permissive action/pampered. Structure and function of family play an important role on parenting model where there is cooperation between family members. Women factory workers used parenting model through (1) habituation, (2) exemplary, (3) advice, (4) giving an awards or punishment. Practice of parenting model was also supported by the factory proved on giving policy which facilitate parenting activities, but they should coordinate in advance with the company. Keywords: Parenting Model, Women Labors, Family, Structural FunctionalÂ Approach.